Outcome of Acute Kidney Injury in Patients with Type 2 Diabetes Mellitus - Iqbal, Sarwar; Haque, Wasim Md Mohosinul; Chowdhury, Tufayel Ahmed; Ananna, Mehruba Alam; Rahim, Muhammad Abdur; Samad, Tabassum; Billah, Md Mostarshid; Bhuiyan, ASM Monzur Morshed; Mitra, Palash (BIRDEM Medical Journal, 2017)
Background: Diabetic patients are more vulnerable to develop acute kidney injury (AKI) when compared to non diabetic counterpart. However, it is not known whether outcome of AKI is variable according to etiology in diabetic subjects. This study was aimed to observe the causes of AKI in diabetic population and to evaluate the outcome. Methods: This cross-sectional study was done in Department of Nephrology, BIRDEM General Hospital, from May 2009 to April 2010. During the study period a total of 50 subjects were included. All cases of AKI and AKI on chronic kidney disease (CKD) were included except AKI due to trauma. Results: AKI due to acute gastroenteritis, non-steroidal anti-inflammatory drugs (NSAIDs),septicemia, gentamicin, obstructive uropathy, rapidly progressive glomerulonephritis (RPGN) comprised 46%, 42%, 4%, 2%,2%, and 4% cases respectively. All cases of AKI due to acute gastroenteritis improved. Among NSAID induced AKI, 26% improved, 6% improved with residual renal damage, 8% did not improve and 1% patient expired. All cases of septicemia induced AKI improved. Patient with gentamicin induced AKI improved with residual renal damage. Patient with obstructive uropathy improved. None of AKI cases due to RPGN improved. Conclusion: It may be suggested that outcome of AKI is variable according to etiology. Outcome is better in AKI due to pre-renal and post-renal causes than AKI due to intrinsic causes. Further study can be done to compare the outcome of AKI according to etiology between diabetic and non-diabetic populations. Birdem Med J 2016; 6(2): 95-99